Language Choice and Use in Training Sessions of Selected Malaysian Public Organisations - Ariffin, Kamisah (2007)
This study examined the language choice and use of the speakers in the formal workplace domain of public organisations in Malaysia. It was the assumption of this study that, other languages understood by the speakers in the context of interaction were also used in public organisations despite the country's policy on the use of the national language, Bahasa Malaysia (BM) for official purposes. The discourse of the organisational training sessions was analysed in terms of the speakers' language choice and use, and the factors governing the choice. The data for the study mainly consist of the transcribed discourse of the training sessions of the selected public organisations. The data were complemented by the data from the survey questionnaire and interview. The factors governing the speakers' choice of language in their interactional context were examined under their societal institutional and socio-psychological levels. The findings could provide insights into a range of perspectives underlying the choice. The data were analysed in two parts: domain analysis and linguistic analysis. The domain analysis described speakers' language use from the socio-psychological and societal levels. In this analysis, observable themes or patterns that emerged from the speakers' speech were discussed to explain the language use within the context of interaction. The linguistic analysis, on the other hand, focused on speakers' choice based on the linguistic and stylistic features inherent in the speakers' speech. These include the language features of colloquial BM and Malaysian English (ME), and the occurrence of code-switching in terms of levels and types, and the discourse functions of code-switching. Evidence from the discourse revealed that the use of BM in formal context as stipulated in the National Language Policy was not really adhered to in the studied organisations. The analysis showed that BM and English were used in varying proportions in the interactional context. The findings also suggested that the language use depended largely on the societal-institutional and sociopsychological levels of the speakers and their communicative intent. The data displayed extensive use of the colloquial BM and the local variety (ME). Another pertinent feature found was the code-switching phenomenon. The data demonstrated that code-switching, both at intra- and inter-sentential levels, emerged as speakers' choice to fulfill various communicative functions in their speech. The study concluded that the stipulated language use in the domain of public organisations had oversimplified the complexities of the actual language use in a multilingual context. Speakers would use any language in their repertoire to suit their communicative needs. The language use could also be influenced by an array of factors from the societal institutional and socio-psychological levels of the speakers. The study also offered a model that could illustrate the pattern of language use in the studied organisations based on the ethnographic and linguistic evidence derived from the data. Finally, the study discussed the theoretical, methodological and sociolinguistic implications of the evidence that may be of interest to those concerned with sociolinguistic research and the country's language planning and its implementation. Some recommendations for further research were also put forward.